Inventory of Raw Materials in Tempe Processing Medium Enterprises With EOQ Approach (Economic Order Quantity) (Case Study of Original Tempe Business of Kendari Nation Hope) - Jannatin Jannatin; Sarinah Sarinah; Muhammad Syukri (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2022)
This study aims to determine: (a) how many times per month the frequency of purchasing raw materials, (b) how much the total cost of raw material supplies determines the Economic Order Quantity (EOQ) Approach policy, and find out what the limit for ordering raw materials is needed during the grace period for the Tempe Asli Harapan Bangsa Medium Enterprises. The type of data used is quantitative data. Data analysis uses the EOQ (Economic Order Quantity) method approach. The results showed that the frequency of ordering soybean raw materials for Tempe Asli Harapan Bangsa medium enterprises in 2020 was 28 times; in 2021, there were 27 orders in one year. The limit or point of ordering raw materials needed when using the EOQ method in 2020 is 63,427 Kg, and in 2021 it is 72,385 Kg. The total cost of the company's raw material inventory, when calculated according to the EOQ for 2020, is IDR 452,620,622; in 2021, it is IDR 471,266,128. So, the total cost of soybean raw material inventory calculated according to the EOQ is greater than that incurred by the Original Harapan Bangsa Tempe Business, so there is an additional cost of soybean raw material inventory when using the EOQ method in preparing soybean raw material.